DIPLOMASI PARALEL KOTA TANGERANG TERHADAP KOTA YANTAI DALAM MENGEMBANGKAN UMKM - Syafa Ratnadewati; Fuad Azmi; Windy Dermawan (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2026)
This research examines the practice of parallel diplomacy conducted by Tangerang City toward Yantai City in the context of Micro, Small, and Medium Enterprises (MSMEs) development. The study is grounded in a constructivist approach in international relations, which conceptualizes diplomacy as a social process shaping identities, interests, and shared meanings among actors. Parallel diplomacy is employed to explain international engagement by subnational and non-state actors operating alongside state diplomacy without full subordination to central government authority. It is analytically distinguished from paradiplomacy through its autonomous, non-hierarchical, and network-based characteristics. The analysis is further supported by the concepts of non-state actors, city diplomacy, and economic diplomacy to capture the roles of local governments, MSMEs, and business communities. Within this framework, MSMEs are positioned as local economic actors and as strategic instruments linking local development objectives with global economic dynamics. This study adopts a qualitative case study design, utilizing in-depth interviews with key informants and analysis of official policy documents and cooperation frameworks. Data are analyzed thematically through an inductive approach, supported by source and method triangulation to ensure analytical rigor. The findings indicate that parallel diplomacy between Tangerang City and Yantai City proceeds through stages of initiation, formulation of mutual understanding via a Letter of Intent, and post-agreement implementation focused on MSMEs facilitation. Parallel diplomacy functions as a supporting instrument for MSMEs' development through network expansion, product promotion, and cross-border business learning, although its implementation remains largely mediated by the local government as facilitator. The study concludes that the effectiveness of parallel diplomacy is shaped by institutional capacity, inter-actor coordination, and alignment with local development policies, while recommending stronger direct MSMEs involvement and further theoretical development of parallel diplomacy within local-actor-based international relations studies. Keywords: Parallel diplomacy, Tangerang City, Yantai City, MSMEs, non-state actors.